FACTORS INFLUENCING UNHOLY PRACTICES OF INDISCRIMINATE DUMP SITE IN WARRI-SOUTH, DELTA STATE, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2024)
The increasing number of indiscriminate dump sites in Warri-south in Delta state is worrisome and adversely affecting the living standard and health conditions of its growing populace. This study seeks to investigate the factors that influence unholy practices of indiscriminate waste disposal and to seek appropriate measures for mitigating or curbing this menace. It employs the cross-sectional research methodology. A sample size of 100 respondents from households living in Warri is used while a structured questionnaire with a three Likert scale is the research instrument for data collection.   Exploratory Data analysis is employed to extract insights to explain the menace of dump site increase and the factors that significantly influence it. The results show that domestic waste such as food, paper, glass, and plastic waste is on the increase due to key influencing factors such as poor waste management laws, lack of waste facilities, poor training of waste collectors, and household attitudes towards waste disposal. Waste segregation and recycling were countermeasures to address waste disposal.
Keywords: Waste disposal; food waste; segregation; recycling; dump site